The uterine cavity state in older reproductive age patients - V. N. Lokshin; A. N. Rybina; A. T. Abshekenova; E. Askar; Sh. K. Karibaeva; R. K. Valiev (Акушерство, гинекология и репродукция)
Introduction. Successful completion of in vitro fertilization (IVF) program is characterized by pregnancy achievement, suggesting that an implantation-competent embryo has reached a receptive endometrium. Chronic endometritis (CE) often being asymptomatic or presented with non-specific symptomsrepresents one of the main causes for impaired endometrial receptivity. CE treatment and normalization of CD138 expression are related to improved outcomes in assisted reproductive technology (ART) programs, primarily in women of advanced reproductive age.Aim: to analyze the frequency and severity of pathological pathological endometrial changes by using hysteroscopy with biopsy and immunohistochemical examination (IHC) in women of advanced (≥ 35 years old) vs. younger (< 35 years old) reproductive age.Materials and Methods. A retrospective descriptive continuous cross-sectional study was conducted to analyze 569 hysteroscopy protocols with biopsy and IHC performed at the PERSONA clinic in 2020–2022. Clinical and anamnestic data (age, frequency of primary and secondary infertility), frequency of uterine cavity pathology, age-related pattern and severity of uterine cavity pathology were assessed according to histological and IHC studies in two age groups: < 35 years and ≥ 35 years.Results. CE was identified in 80.47 % of younger and 85.3 % of older patients. Severe CE was significantly more common in ≥ 35-year-old women (12.73 % vs. 3.6 %; p = 0.021). No significant inter-group differences were found in CD138 expression levels. Common endometrial abnormalities included fibrosis, stromal sclerosis, lymphocytic infiltration, polyps, hypoplasia, hyperplasia, and mixed lesions.Conclusion. While overall endometrial pathology was commonly observed in both age groups, severe CE forms were significantly more frequent in women of advanced reproductive age. Office hysteroscopy is recommended prior to ART initiation in this population to optimize outcomes.